2016
DOI: 10.1007/s10265-016-0886-0
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA-binding protein DRB3 negatively regulates anthocyanin biosynthesis by modulating PAP1 expression in Arabidopsis thaliana

Abstract: The model plant Arabidopsis thaliana has five double-stranded RNA-binding proteins (DRB1-DRB5), two of which, DRB1 and DRB4, are well characterized. In contrast, the functions of DRB2, DRB3 and DRB5 have yet to be elucidated. In this study, we tried to uncover their functions using drb mutants and DRB-over-expressed lines. In over-expressed lines of all five DRB genes, the over-expression of DRB2 or DRB3 (DRB2ox or DRB3ox) conferred a downward-curled leaf phenotype, but the expression profiles of ten small RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…pap1‐D is an activation tagging mutant with an enhanced expression of MYB75 , which is a master regulator of the anthocyanin biosynthesis pathway (Borevitz et al., ). Due to the activation of MYB75 in pap1‐D , several genes encoding key enzymes in anthocyanin biosynthesis (e.g., chalcone synthase, dihydroflavonol reductase, and anthocyanidin synthase) are upregulated in this mutant, resulting in its overproduction of anthocyanin (Sawano et al., ). ref2 and b2b3 are mutants with defects in the enzymes involved in the biosynthesis of defense compounds called glucosinolates (Zhao et al., ; Hemm et al., ).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…pap1‐D is an activation tagging mutant with an enhanced expression of MYB75 , which is a master regulator of the anthocyanin biosynthesis pathway (Borevitz et al., ). Due to the activation of MYB75 in pap1‐D , several genes encoding key enzymes in anthocyanin biosynthesis (e.g., chalcone synthase, dihydroflavonol reductase, and anthocyanidin synthase) are upregulated in this mutant, resulting in its overproduction of anthocyanin (Sawano et al., ). ref2 and b2b3 are mutants with defects in the enzymes involved in the biosynthesis of defense compounds called glucosinolates (Zhao et al., ; Hemm et al., ).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…() reported that miR858 negatively regulates anthocyanin biosynthesis by modulating the expression of two R2R3 MYB TFs. A dsRNA binding protein DRB3 negatively regulates anthocyanin biosynthesis by modulating PAP1 expression in Arabidopsis (Sawano et al ., ). Xie et al .…”
Section: Discussionmentioning
confidence: 97%
“…This class of RBPs harbors an evolutionarily conserved, double-stranded RNA (dsRNA)binding domain (dsRBD)/dsRNA-binding motif (dsRBM) [76]. Plant proteins can have one or more DSRM, and each is comprised of 65 conserved amino acids with a characteristic (α1-β1-β2-β3-α2) fold that interact with double-stranded RNAs [12,76]. Studies with Arabidopsis DRBPs revealed their association with small plant RNA biogenesis pathways [120].…”
Section: Double-stranded Rna-binding Protein (Drbp)mentioning
confidence: 99%
“…Five DRBPs (DRBP1-5) were reported in Arabidopsis. Of these, overexpression of DRB2 and DRB3 exhibited salt tolerance [76]. Upon exposure to cold stress conditions, drb2 and drb3 mutants enhanced the accumulation of anthocyanins by regulating anthocyanin biosynthesis genes.…”
Section: Double-stranded Rna-binding Protein (Drbp)mentioning
confidence: 99%